Chemotaxis in Escherichia coli proceeds efficiently from different initial tumble frequencies. - Weis, R M (1990)
The relationships between the level of tumbling, tumble frequency, and chemotactic ability were tested by constructing two Escherichia coli strains with the same signaling apparatus but with different adapted levels of tumbling, above and below the level of wild-type E. coli. This was achieved by introducing two different aspartate receptor genes into E. coli: a wild-type (wt-tars) and a mutant (m-tars) Salmonella typhimurium receptor gene. These cells were compared with each other and with wild-type E. coli (containing the wild-type E. coli aspartate receptor gene, wt-tare). It was found that in spite of the differences in the adapted levels of tumbling, the three strains had essentially equal response times and chemotactic ability toward aspartate. This shows that the absolute level of the tumbling can be varied without impairing chemotaxis if the signal processing system is normal. It also appears that a largely smooth-swimming mutant may undergo chemotaxis by increasing tumbling frequency in negative gradients.